Internet (self) representations of the Peruvian Private Security Guards in Iraq - Migliori, Giuliana (2019)
This article analyzes the self-representations in social media of a group of Peruvian workers hired as Private Security Guards in Iraq (2005-2012), as well as their different identifications referring to the hypermedia narratives of the Internet, about the globalized culture and regulated by the military workforce of transnational companies. In addition to the strong nationalist roots consistent with the authoritarian and classist tradition of Peruvian society and the realization of their manhood, these identities manifest an autographic and epic presence of seasonal migration experiences through their videos and interactive environments. As well as strengthening the social construct embodied by the mercenary, this this type of guard is a sign of contemporary civility that helps regulate the system. Its legal and supposedly neutral status collides with an empirical position of combatant giving way to a critical social role. In this, the paradox of a prototype of a subject adapted to the market economy would be possible thanks to a war and the strengthening of masculinity patterns specific to the local context.